Ancestry and genetic structure of resident and anadromous rainbow trout ( Oncorhynchus mykiss ) in Argentina - Carolina Lázari; Carla Riva‐Rossi; Javier Ciancio; Miguel Pascual; Anthony J. Clemento; Devon E. Pearse; John Carlos Garza (Journal of Fish Biology, 2024)
Since the first introduction from North America more than a century ago, rainbow trout ( Oncorhynchus mykiss ) have rapidly established self‐sustaining populations in major river basins of Patagonia. Many generations later, only the freshwater resident life history is expressed in the Chubut and Negro rivers of northern Argentinian Patagonia, whereas both the resident and anadromous life histories are found in the Santa Cruz River of southern Argentina. Despite previous studies that have tried to identify the sources of these introduced populations, uncertainty still exists. Here we combined data from many single‐nucleotide polymorphisms and microsatellite loci in O. mykiss populations from Argentina and North America to evaluate putative source populations, gene flow between Argentinian river basins, and genetic diversity differences between Argentinian and North American populations. We found that populations from northern and southern Patagonia are highly differentiated and have limited gene flow between them. Phylogeographic analysis also confirmed that they have separate origins, with the northern populations most closely related to the domesticated rainbow trout strains that are raised worldwide and the Santa Cruz River populations most closely related to North American populations from California and Oregon that have an anadromous component. In addition, fish with different life histories in the Santa Cruz River were found to constitute a single interbreeding population. No evidence was found of reduced genetic variation in introduced rainbow trout, suggesting multiple contributing sources. In spite of these advances in understanding, significant questions remain regarding the origins and evolution of the introduced O. mykiss in Patagonia.